Cancers Attributable to Infectious Agents: an Ecological Study in Asia - Khazaei, Zaher; Moradi, Yousef; Adineh, Hossein Ali; Rezaei, F; Sohrabivafa, Malihe; Darvishi, Isan; Dehghani, Seyedeh Leila; goodarzi, Elham (Asian Pacific Journal of Environment and Cancer, 2018)
Infections are a major contributor to cancer, especially in developing countries. Infections through the virus, bacteria and parasites are the most and most preventable causes of cancer in the world. The aim of the current study was to investigate the epidemiology of cancer-related infections in Asia. We considered 4 infectious agents classified as carcinogenic to human beings by the International Agency for Research on Cancer. We calculated the number of new cancer cases in 2012 attributable to infections by country, by combining cancer incidence estimates (from GLOBOCAN 2012) with the estimates of attributable fraction (AF) for the infectious agents. AF estimates were calculated from the prevalence of infection in cancer cases for the infection (for some sites). According to data registered in 2012, about 14 million new cases of cancer were detected worldwide of which 2. 2 million people (15.4%) diagnosed with cancer due to infection. The highest incidence of infectious cancers related to the African continent with a prevalence of 27.6% followed by Asian continents (21.4%), America (7.9%), Europe (7.3%) and Oceania (4.8%), respectively. In the Asian continent, of all cancers associated with infection in males, 48.1% were related to Helicobacter pylori infection, 33.2% of hepatitis B virus, 8% of hepatitis C and 3.3% of HPV and in women 47.4% HPV, 28.7% Helicobacter pylori, 15.3% Hepatitis B and 4.5% Hepatitis C, respectively. India (230,000 cases) and Japan (140,000 cases) were the most affected, while Bahrain (86 cases) and Brunei (88 cases) had the least cases of infection-related cancer. in Asia, the most common cancer-related infection in males and females were reported for Helicobacter pylori and HPV, respectively. Therefore, with preventive interventions aimed at reducing these infections, the burden of cancers can be reduced.